Doing Business in Indonesia 2012 - World Bank (Washington, DC, 2013)
Doing Business in Indonesia 2012 is the second subnational report of the doing business series in Indonesia. In 2010, quantitative indicators on business regulations were analyzed for 14 cities: Balikpapan, Banda Aceh, Bandung, Denpasar, Jakarta, Makassar, Manado, Palangka Raya, Palembang, Pekanbaru, Semarang, Surabaya, Surakarta, and Yogyakarta. This year, doing business in Indonesia 2012 documents improvements in the 14 cities previously measured and expands the analysis to 6 new cities across the nation: Batam, Gorontalo, Jambi, Mataram, Medan, and Pontianak. Doing business investigates the regulations that enhance business activity and those that constrain it. Regulations affecting 3 stages of the life of a business are measured at the subnational level in Indonesia: starting a business, dealing with construction permits, and registering property. These indicators were selected because they cover areas of local jurisdiction or practice. The indicators are used to identify business reforms and the extent to which these have been effective in simplifying the procedures, saving time, and lowering the cost of doing business. The data in doing business in Indonesia 2012 are current as of July 2011.